Career Preparation in Agricultural Resources A Curriculum Guide for High School Vocational Agriculture. Test Edition - Householder, Larry; Ohio State Univ., Columbus. Ohio Career Education and Curriculum Management Lab. in Agricultural Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This curriculum guide in agricultural resources is one of 10 guides developed as part of a vocational project stressing agribusiness, natural resources, and environmental protection. The scope of this guide includes eight occupational subgroups: fish, forestry, mining area restoration, outdoor recreation, soil, range, water, and wildlife. It is meant as an aid to all who are involved in the curriculum planning phases prior to classroom instruction. Each unit has seven elements to be used for developing specific curriculum and curriculum materials: unit concept, student performance objectives, instructional areas, examples of learning activities, examples of evaluation processes, instructional materials or equipment, and references. Appendixes list recommended materials and equipment, additional references, and selected professional and technical societies. (Author/JC)
Availability: Agricultural Education Curriculum Materials Service, Room 254, 2120 Fyffe Road, The Ohio State University, Columbus, Ohio 43210 ($4.00).
Sponsoring Agency: Bureau of Occupational and Adult Education (DHEW/OE), Washington, DC.
ERIC Note: For related documents, see CE 002 036-045.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agricultural Education; Agricultural Skills; Behavioral Objectives; Career Education; Conservation Education; Curriculum Development; Curriculum Guides; Environmental Education; Forestry; Land Use; Learning Activities; Natural Resources; Occupational Clusters; Off Farm Agricultural Occupations; Secondary Education; Teaching Guides; Vocational Education; Wildlife Management; Guides, General